Ragam Permainan Tradisional dalam Menstimulasi Aspek Perkembangan Anak Tunagrahita: Sebuah Literature Review - Shinta Maharani Gunawan, Ni Putu; Desira Swandi, Ni Luh Indah (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This research aims to determine traditional games that stimulate the development aspect of mentally retarded children. The method used in this research is a literature review which analyzes relevant articles that meet the research criteria. Based on the results of a review of the previous literature, it was found that there were eight traditional games identified as being able to stimulate development in cognitive, motoric, and social-emotional aspects in mentally retarded children. The application of traditional games in the world of education can be a strategy that supports the learning and development process of mentally retarded children.